A Special SME: An Integrative Literature Review of the Relationship between Instructional Designers and Faculty in the Design of Online Courses for Higher Education. Issue 4 (22nd July 2020) - Chen, Yuan; Carliner, Saul
Abstract : Along with the increase in online courses offered by higher‐education institutions there is a corresponding increase in the number of instructional designers designing and developing these courses. A growing body of literature has emerged exploring the working relationship between instructional designers and faculty in designing online courses in higher education. The purpose of this study is to conduct an integrative literature review to gain a better understanding of the working relationships between faculty and instructional designers. The results provided insights as to how those two parties are working together in designing online courses, and they summarized the factors that affect their relationships. The literature specifically characterizes the relationship between the two parties as collaborative, although it neither defines the concept nor identifies the characteristics of collaboration. The study suggests exploring perspectives of faculty and administrators (who oversee the relationship) in future studies and suggests also that the concept of collaboration needs to be characterized more concretely and explicitly.